Durability evaluation of recycled aggregate concrete in a complex environment. (10th November 2020) - Zhu, Pinghua; Hao, Yali; Liu, Hui; Wang, Xinjie; Gu, Lei
Abstract: In the era of increasing consumption of natural aggregate, recycling construction wastes to prepare structural concrete is an effective measure to solve the dual pressure of resource shortage and environmental pollution. However, the utilization rate of recycled coarse aggregate (RCA) in China is still relatively low. In order to better improve the efficient utilization of waste concrete in the complex environment, the durability resistance of RAC with diverse substitution rates under the coupled action of freezing-thawing (F-T) cycles and chloride attack was investigated in this paper. And the mechanical properties and chloride penetration tests were performed every 100 F-T cycles. The results suggest that frost damage plays a significant promoting role in chloride penetration. Although the physical and mechanical properties decrease gradually as F-T cycles and substitution rates increase, the RAC still could reach at least 50 year of service life in the combined environment of F-T cycles and chloride attack. In addition, the application of RAC in engineering construction can save the raw material cost and disposal fee of RCA, and generate considerable economic benefits and social value. Graphical abstract: Image 1 Highlights: It is imperative to improve the high efficiency utilization of waste concrete. Utilizing 100% of RCA for structural concrete in a complex environment is feasible. The durability of RAC tends to deteriorate as substitution rate of RCA increase. Freeze-thaw cycles have a considerable effect on chloride penetration of RAC. RAC presents a significant advantage in the economic benefits and social value.